Pengaruh Kelayakan Hidup Dan PDRB Terhadap Tingkat Kemiskinan: Studi Pada 10 Provinsi Termiskin Di Indonesia - Sagala, Eliza Clara Yeremia; Muchtar, Masruri; Sihombing, Pardomuan Robinson (Ecoplan, 2024)
To get out of the Middle-Income Trap, Indonesian economic growth must be consistently above 6% annually. In addition, the reduction in poverty rates is also an important indicator that Indonesia will emerge from this trap. The study aims to determine the impact of Provincial Minimum Wage (UMP), Gross Regional Domestic Product (PDRB), and Human Development Index (IPM) on Poverty Rate in the ten poorest provinces in Indonesia. Using data from the Badan Pusat Statistik for 2012-2022, this research adopts linear regression of multiple data panels. The results show that all variables simultaneously affect the poverty rate significantly. Partially, UMP positively and significantly impacts the poverty rate, while IPM has a negative effect. PDRB has no significant influence on the poverty rate. It implies that the government should review the increase in UMP to stay at the point of balance. Economic growth must consider the level of well-being of all segments of society.